Analysis Of Musculoskeletal Disorders (Msds) Risk Factors In Workers At The Sanan Malang Tempe Chips Industry Center - Kristiana Yulianti; Fresvian Jenrivo; Ani Asriani Basri; Fariz Zuvil Arganata (Universitas Muhammadiyah Malang, 2025)
Introduction: Informal industries in Indonesia still use the labor of workers rather than existing technology. One of the informal industries in Indonesia is the chip industry. Workers in the informal tempe chips industry in the production process have different work activities and work duration. The purpose of this study was to analyze risk factors with Musculoskeletal Disorders. Methods: This research method is quantitative with purposive sampling technique on 33 workers using Fisher's Exact Test analysis with SPSS 26. The research instruments are Nordic Body Map (NBM), stopwatch, and Rapid Upper Limb Assessment (RULA). Results: Based on the results of the analysis, the significance value of work posture with Musculoskeletal Disorders is 0,021 < 0,05 and work duration with Musculoskeletal Disorders is 0,021 < 0,05. Work posture factors and work duration have a significant relationship with Musculoskeletal Disorders. Conclusion: If workers work in an unergonomic posture, it can cause MSDs. Likewise, if workers work in static conditions, such as standing when frying, and sitting when cutting tempeh or packing chips for a long time, this can trigger pain in several parts of the body or symptoms of MSDs.